2013
DOI: 10.1093/brain/awt163
|View full text |Cite
|
Sign up to set email alerts
|

A novel frontal pathway underlies verbal fluency in primary progressive aphasia

Abstract: The frontal aslant tract is a direct pathway connecting Broca's region with the anterior cingulate and pre-supplementary motor area. This tract is left lateralized in right-handed subjects, suggesting a possible role in language. However, there are no previous studies that have reported an involvement of this tract in language disorders. In this study we used diffusion tractography to define the anatomy of the frontal aslant tract in relation to verbal fluency and grammar impairment in primary progressive apha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
358
3
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 417 publications
(407 citation statements)
references
References 45 publications
31
358
3
3
Order By: Relevance
“…FAT's name is derived from its oblique shape and it consists of short association connections between the posterior part of the inferior frontal gyrus (IFG) and the posterior region of the superior frontal gyrus (SFG) [5]. Diffusion tractography imaging (DTI) showed that FAT connects pre-supplementary/supplementary motor area (pre-SMA/SMA) with Broca's region, corresponding to the Brodmann areas 8.9 and 44.45, respectively [3-5, 17, 19].…”
Section: Introductionmentioning
confidence: 99%
“…FAT's name is derived from its oblique shape and it consists of short association connections between the posterior part of the inferior frontal gyrus (IFG) and the posterior region of the superior frontal gyrus (SFG) [5]. Diffusion tractography imaging (DTI) showed that FAT connects pre-supplementary/supplementary motor area (pre-SMA/SMA) with Broca's region, corresponding to the Brodmann areas 8.9 and 44.45, respectively [3-5, 17, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, damages of this bundle have been previously associated with various degrees of speech impairment, from total inability to initiate speech (i.e., mutism) to mild altered fluency [48]. The microstructural damage of FAT was also previously found associated with verbal fluency deficits, mainly in patients with the agrammatic-variant of PPA [14]. In this variant of PPA, patients show several languages' deficits including the "apraxia of speech" [49], a deficit in which the motor engrams needed to produce verbal speech are lost in the absence of motor impairments.…”
Section: Discussionmentioning
confidence: 92%
“…The role of FAT has been previously investigated in patients showing languages disorders due to different conditions, such as neurodegenerative disorders (e.g. primary progressive aphasia) [14] or focal brain lesions (e.g. brain tumors).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations